DETERMINAN KINERJA PACKAGING CKD EKSPOR BERBASIS KPI - Damay Setiawan; Abdullah Rakhman (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study examines the determinants of CKD export packaging performance based on process Key Performance Indicators in an automotive manufacturing company. The study used secondary monthly operational data from April 2020 to March 2025, resulting in 60 observations. The analyzed variables include Safety, Quality, Productivity, Cost, Container Efficiency, Employee Attendance, and Employee Idea Suggestion. Data were analyzed using Partial Least Squares Structural Equation Modeling with WarpPLS. The results show that Cost is the most dominant determinant and has a positive significant effect on CKD export packaging performance. Employee Attendance also has a positive significant effect, indicating the importance of workforce stability in maintaining output realization. Productivity shows a marginal positive effect, while Safety and Quality function as baseline requirements. Container Efficiency shows a marginal negative relationship, indicating a potential trade-off between load density and process stability. Employee Idea Suggestion has a negative significant effect in the same period, suggesting short-term disruption, trial, adjustment, and learning-curve effects. The study concludes that CKD export packaging performance is mainly driven by cost efficiency and attendance stability.